"A Clean Break": Clara Zetkin, the Socialist Women's Movement, and Feminism. Issue 2 (3rd April 2018) - Gaido, Daniel; Frencia, Cintia
ABSTRACT: The movement of proletarian women of the Social Democratic Party of Germany, and by extension of the Second International (1889–1914), was structured by Clara Zetkin around the principle of a "clean break" between the women of the exploiting and exploited classes, which laid the programmatic foundations for the development of a mass movement of socialist working women that eventually grew to have 174, 754 members in 1914. This movement, whose central axis was the magazine Die Gleichheit edited by Zetkin, had as its central organizational proposition the idea that Marxism, as a working-class political tendency, and feminism, as a multi-class movement, were incompatible, and that therefore working-class women had to have their own organizations within socialist parties which also included working-class men. The International Socialist Women's Movement, which celebrated its first conference in Stuttgart in 1907 and adopted universal female suffrage as its central transitional slogan, was responsible for the proclamation of International Women's Day by the Second International Socialist Women's Conference held in Copenhagen in 1910. The Russian Revolution started with demonstrations organized by the working women of Petrograd to celebrate International Women's Day. The article closes with a brief assessment of the legacy of the proletarian women's movements.